2018
DOI: 10.1039/c8ra04547j
|View full text |Cite
|
Sign up to set email alerts
|

A study on fabrication of PVDF-HFP/PTFE blend membranes with controllable and bicontinuous structure for highly effective water-in-oil emulsion separation

Abstract: PVDF-HFP/PTFE blend membranes were prepared for the first time via TIPS method with DBP and DOP as mixed diluent and PTFE as the blending polymer. The obtained membranes could separate different water-in-oil emulsions effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…As the density of the PDMS microsphere aerogel is much lower than that of PVDF nanofibers, the PDMS microspheres are suspended in the high-voltage electric field, which descend slowly and mainly coat on the nanofiber surface. Consequently, Si elements could be only observed on the microspheres, while the F elements appear on both the microspheres and the nanofibers. The structure of the PVDF/PDMS nanofiber membranes is similar to the results reported previously. During this process, the monomers of PDMS solution and PVDF solution could hardly be mixed uniformly in the needles; however, the PVDF solution and PDMS solution could still diffuse each other. The PDMS microspheres could be formed at first since the viscosity of the outer solution is not high enough to form stable a Taylor’s cone. , Notably, some of the PVDF solution diffused into the outside solution surrounded by the PDMS microspheres, as THF evaporates more quickly than DMF. Due to the solidification of the PDMS, the evaporation rate of DMF becomes slower.…”
Section: Resultssupporting
confidence: 83%
“…As the density of the PDMS microsphere aerogel is much lower than that of PVDF nanofibers, the PDMS microspheres are suspended in the high-voltage electric field, which descend slowly and mainly coat on the nanofiber surface. Consequently, Si elements could be only observed on the microspheres, while the F elements appear on both the microspheres and the nanofibers. The structure of the PVDF/PDMS nanofiber membranes is similar to the results reported previously. During this process, the monomers of PDMS solution and PVDF solution could hardly be mixed uniformly in the needles; however, the PVDF solution and PDMS solution could still diffuse each other. The PDMS microspheres could be formed at first since the viscosity of the outer solution is not high enough to form stable a Taylor’s cone. , Notably, some of the PVDF solution diffused into the outside solution surrounded by the PDMS microspheres, as THF evaporates more quickly than DMF. Due to the solidification of the PDMS, the evaporation rate of DMF becomes slower.…”
Section: Resultssupporting
confidence: 83%
“…Membrane emulsification is commonly used to produce O/W emulsions. Only a few studies have reported its utilization in preparing W/O emulsions with hydrophobic membranes such as hydrophobic Shirasu‐porous‐glass (SPG) membrane, ceramic membrane, and polytetrafluoroethylene (PTFE) membrane (Alliod, Messager, Fessi, Dupin, & Charcosset, ; Wang et al., ; Wu, Jing, Xing, & Xu, ). The particle size of W/O emulsion is highly dependent on the interfacial tension between water and oil phases, emulsifier concentration, membrane pressure, and the pore size of membranes.…”
Section: Formation Of W/o Emulsions: Emulsification Methodsmentioning
confidence: 99%
“…[6][7][8] Flexible polymer-based membranes have received a lot of interests because they have shown outstanding and unique superiorities. Nowadays, various polymer membranes have been developed, such as polystyrene, 8 polyacrylonitrile, 9,10 polyimide, 11 polysulfone, 12 polyvinylidene fluoride, 13,14 polypropylene, 7 polyurethane 15 and so forth. Among them, nanofiber polymer membranes further have virtues as high porosity, large specific surface area, and homogeneity of fiber pore size.…”
Section: Introductionmentioning
confidence: 99%